Extracellular Matrix Protein Ratios in the Human Heart and Vessels: How to Distinguish Pathological From Physiological Changes? - Wittig, Corey; Szulcek, Robert (Frontiers in Physiology, 2021)
Cardiovascular pathology is often accompanied by changes in relative content and/or ratios of structural extracellular matrix (ECM) proteins within the heart and elastic vessels. Three of these proteins, collagen-I, collagen-III, and elastin, make up the bulk of the ECM proteins in these tissues, forming a microenvironment that strongly dictates the tissue biomechanical properties and effectiveness of cardiac and vascular function. In this review, we aim to elucidate how the ratios of collagen-I to collagen-III, and elastin to collagen, are altered in cardiovascular diseases and the aged individuum. We elaborate on these major cardiovascular ECM proteins in terms of structure, tissue localization, turnover, and physiological function, and address how their ratios change in aging, dilated cardiomyopathy, coronary artery disease with myocardial infarction, atrial fibrillation, aortic aneurysms, atherosclerosis, and hypertension. To the end of guiding in vitro modeling approaches, we focus our review on the human heart and aorta, discuss limitations in ECM protein quantification methodology, examine comparability between studies, and highlight potential in vitro applications. In summary, we found collagen-I relative concentration to increase or stay the same in cardiovascular disease, resulting in a tendency for increased collagen-I/collagen-III and decreased elastin/collagen ratios. These ratios were found to fall on a continuous scale with ranges defining distinct pathological states, as well as a significant difference between the human heart and aortic ECM protein ratios.